A4NH 2017 annual report - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2018)
The CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) is dedicated to the realization of Sustainable Development Goals 2 and 3, laid out by the United Nations. In 2017, A4NH began its second phase of work, with five research flagships, seven managing partners, and activities in more than 30 countries all working toward realizing this vision.